2005
DOI: 10.1542/peds.2005-1287
|View full text |Cite|
|
Sign up to set email alerts
|

Unexpected Increased Mortality After Implementation of a Commercially Sold Computerized Physician Order Entry System

Abstract: We have observed an unexpected increase in mortality coincident with CPOE implementation. Although CPOE technology holds great promise as a tool to reduce human error during health care delivery, our unanticipated finding suggests that when implementing CPOE systems, institutions should continue to evaluate mortality effects, in addition to medication error rates, for children who are dependent on time-sensitive therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
663
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 948 publications
(680 citation statements)
references
References 20 publications
7
663
0
10
Order By: Relevance
“…This fits into our "Overdependence on technology" unintended consequence category. No one mentioned that the system might cause "New kinds of errors" which we and others [3,4,5,8] have seen and documented at many different CPOE implementation sites. Further, none of the interviewees mentioned that the new system might have a detrimental impact on communication.…”
Section: Discussion Survey Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fits into our "Overdependence on technology" unintended consequence category. No one mentioned that the system might cause "New kinds of errors" which we and others [3,4,5,8] have seen and documented at many different CPOE implementation sites. Further, none of the interviewees mentioned that the new system might have a detrimental impact on communication.…”
Section: Discussion Survey Resultsmentioning
confidence: 99%
“…While there have been several excellent articles describing impressive improvements in patient safety, decreases in patient costs due to decreases in redundant laboratory testing, and increased compliance with quality of care guidelines [see 2 for an excellent review of this literature], there have also been several articles describing significant negative, and often unanticipated occurrences that our research group along with others have identified [e.g., 3,4,5,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the implementation of some new EHR systems has resulted in unexpected and deleterious consequences. 1,2 If health care organizations can successfully tailor the process of implementing new EHR systems to make the transition safer and more efficient, then the enhancements they offer to health care practitioners will likely be realized more rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Rates for non-abbreviation prescribing errors, however, were actually highest at 12 weeks post-implementation, suggesting that transitioning between systems may pose potential patient safety threats even for experienced e-prescribers. Previous studies have identified unintended negative consequences from the introduction and use of computerized systems for ordering medications, including the facilitation of errors 36,37 . Also in our study, overall error rates for nonabbreviation errors were no different at one year and baseline, despite the fact that the old system had very limited CDS, although due to our small sample size, we may not have been able to detect a significant difference.…”
Section: Discussionmentioning
confidence: 99%